2019
DOI: 10.21203/rs.1.10/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Postoperative Visual Performance Between Bifocal and Trifocal Intraocular Lens Based on Randomized Controlled Trails: A Meta-Analysis

Abstract: Background:To compare the clinical performance of bifocal and trifocal intraocular lenses (IOLs) in cataract surgery, a meta-analysis on randomized controlled trials was conducted. Methods: A comprehensive literature retrieval of PubMed, Science Direct and EMBASE was performed in this systematic review. Clinical outcomes included visual acuity (VA), contrast sensitivity (CS), spectacle independence, postoperative refraction and surgical satisfaction. Results: There were 8 RCTs included in this study. The dif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…As patients can no longer accommodate after IOL implantation, they need to use spectacles to see other distances in focus. e first-generation "bifocal" IOLs provided two focal points, one for far and the other for near vision, but thanks to an upsurge in computer, tablet, and smartphone use over recent years, there has been an upsurge in demand for IOLs that offer good intermediate vision too-something that bifocal IOLs cannot achieve [1]. In 2010, the first trifocal IOL (FineVision Micro F, PhysIOL, Liège, Belgium) was introduced [2], and numerous studies have shown that this IOL provides good far, intermediate, and near visual acuities (VA) and results in high levels of patient satisfaction [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…As patients can no longer accommodate after IOL implantation, they need to use spectacles to see other distances in focus. e first-generation "bifocal" IOLs provided two focal points, one for far and the other for near vision, but thanks to an upsurge in computer, tablet, and smartphone use over recent years, there has been an upsurge in demand for IOLs that offer good intermediate vision too-something that bifocal IOLs cannot achieve [1]. In 2010, the first trifocal IOL (FineVision Micro F, PhysIOL, Liège, Belgium) was introduced [2], and numerous studies have shown that this IOL provides good far, intermediate, and near visual acuities (VA) and results in high levels of patient satisfaction [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of trifocal IOLs in providing better intermediate vision than bifocal IOLs has been reported in several studies [73]. The excellent intermediate vision is also shown in a prospective trial of refractive lens exchange (no clinically significant cataract present) from 2016 that evaluates the visual acuity after implantation of a trifocal IOL (AT LISA, Zeiss, Germany) in patients with a crystalline lens.…”
Section: Resultsmentioning
confidence: 75%